Pengembangan Song, Word Map, Game dan Role Play dalam Pembelajaran Bahasa Inggris untuk Meningkatkan Speaking Skill dan Keterlibatan Siswa Kelas III SD Kristen Pelita Bangsa Lumajang - Endah Dwi Lestari (Ilmiah Manajemen Bisnis, 2019)
Abstract — Speaking skill is one of productive skill in English subject but most of the third graders of Pelita Bangsa Christian Primary School Lumajang had diffculties to develop and increase their speaking ability. The result of students’ speaking test showed only 54% of students had passed the minimum score and 62% of students engaged during the class. This classroom action research aimed to improve the students’ ability to speak English and their engagement through the development of song, word map, game and role play technique. The subjects in this study were thirteen students of third grade in Pelita Bangsa Christian PrimarySchool Lumajang by using Kemmis and Taggart model. It was implemented through two cycles and conducted from November 2013 until May 2014. The results of students’ speaking test showed that the development of song, word map, game and role play technique improved the students’ speaking skill up to minimum score from 54% (before CAR) to 69% in cycle 1 and to 84,6 % in cycle 2. While the students’ engagement had increased from 62% (before CAR) to 85% in cycle 2. In conclusion, the development of song, word map, game and role play technique improved speaking skill and engagement of the third graders of Pelita Bangsa Christian Primary School Lumajang. Keywords — song, word map, game dan role play, speaking skill